The Algebraic Equivalence of the Oberhofer-Kmenta and Theil-Boot Formulae for the Asymptotic Variance of a Characteristic Root of a Dynamic Econometric Model - Schmidt, Peter (Econometrica, 1974)
Peter Schmidt, The Algebraic Equivalence of the Oberhofer-Kmenta and Theil-Boot Formulae for the Asymptotic Variance of a Characteristic Root of a Dynamic Econometric Model, Econometrica, Vol. 42, No. 3 (May, 1974), pp. 591-592